Impacts of agricultural extension and environmental factors on technical efficiency of Thai paddy farms using data envelopment analysis approach - Taraka, Kallika; Shamsudin, Mad Nasir; Abd. Latif, Ismail; Ahmed, Abdullahi Farah (Centre for Extension, Entrepreneurship and Professional Advancement (APEEC), Universiti Putra Malaysia, 2010)
This paper adopts Data Envelopment Analysis Approach (DEA) and Tobit Regression Model to measure technical efficiency of paddy farms in the Central region of Thailand and determine the agricultural extension factors which influence the technical inefficiency of farmers. The cross-sectional data in the crop year 2009/2010 were randomly collected from 263 farmers who operated their farms by broadcasting methods. The variables consist of the data in production namely paddy yield, seed, fertilizers, pesticides, fuels and wage in order to measure technical efficiency; and the data about individual farmers’ demographic and socio-economic factors as well as agricultural extension and environmental factors in order to determine the factors affecting technical inefficiency. The empirical results show that the estimated technical efficiencies of the farmers ranged between 0.04 per cent and 100 per cent while the mean level of technical efficiency is 52.3 per cent. Technical efficiency is influenced by age and educational level of farmers. Attendance in Food Safety Training Project and Communicating directly with extension officers are also important factors in contributing positive impact on the level of technical efficiency. This implies that Agricultural Extension Service and Training can enhance higher farm efficiency. Therefore, government should provide the accessible channel linked between officers and farmers as well as improve training program to serve their needs and stimulate farmers to increase their production efficiency.